BASIC HUMAN NEEDS IN THE PERSPECTIVE OF ISLAMIC EDUCATION AND PARTICIPATION IN EDUCATION - Ulfa Aulia; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
The motivation behind this examination is to describe the progress of businesses that depend on environmental potential through strengthening the local area which consists of several stages including training, products and presentation efforts according to the limitations experienced. This investigation uses a subjective methodology that utilizes important information gathered through meetings, perceptions and documentation. The test subjects consisted of residents studying Paket C were local pioneers. The validity of the information utilizes triangulation of sources, strategies and speculation. Information investigation as an intelligent model combines various kinds of information, decline, display and range determination. This exploration resulted in a strengthening program in the repair cycle carrying out preparations for the manufacture of wooden watches. The creation is carried out by learning residents after paket A, B, and C after completing the learning packages. Performances are shown through progress in various media and their share of the entire industry, both at home and abroad. the limited working time of long learning residents